Development of Augmented Reality Based Learning Media on The Topic of Spatial Geometry for Elementary School Students - Lina Anggita Ahsani; Nepsta Ellynlouis Berthania; Anggraita Putri Kumala Dewi; Ulfatun Nisa Asy Syifa (Universitas Pendidikan Indonesia (UPI), 2022)
Spatial structures are three-dimensional buildings that contain space or volume within them and are bounded by sides. The rapid advancement of technology in the world of information technology and computers has also influenced the field of education, offering various conveniences and innovations. Augmented Reality (AR) is a technology that can combine two-dimensional or three-dimensional virtual objects into a real environment and then project these virtual objects in real-time. With AR technology, it is expected to provide innovation in the creation of learning media and new learning experiences in understanding and studying spatial structures, thereby attracting the interest of elementary school students to learn this subject matter.